Tetrahedrite Thermoelectrics: From Fundamental Science to Facile Synthesis - Weller, Daniel P.; Morelli, Donald T. (Frontiers in Electronic Materials, 2022)
Thermoelectric materials have a long and storied history in the research and development of semiconductor materials, being the first such class of materials to be investigated. Thermoelectric may be used to convert heat to electricity or, alternatively, to liberate or absorb heat upon electrical excitation. They thus find application in thermoelectric generators for converting heat from a primary source or a waste stream to useful electrical power, and as solid state heating and cooling devices. In spite of their great potential in such important applications, thermoelectrics have suffered from a number of drawbacks that have hindered their utilization on a large scale. Chief among these is the fact that most high performance thermoelectric materials are comprised of elements that are in relatively low abundance. Additionally, their synthesis typically involves complex and multi-step processes, hindering manufacturability. Thermoelectric materials derived from Earth-abundant sources are thus of strong current interest, from both scientific and economic points of view. One of these, the family of semiconductors based on tetrahedrite compounds, has generated enormous interest over the last decade due to not only its potential low cost, but also for its fascinating science. In this review, we summarize the state of the art of tetrahedrite as a thermoelectric, with special emphasis on the relationship between crystal structure and bonding in the crystal and its unusually low lattice thermal conductivity; on its fascinating electronic structure; and on the wide array of compositions that have been synthesized and whose thermoelectric properties have been studied. We further highlight some rapid and facile synthesis techniques that have been developed for these compounds which, in combination with their potential low material cost, may open the door to widespread application of these fascinating materials.